Pemenuhan Unsur Kesengajaan Pada Delik Promosi Judi Online Terkait Ketidaktahuan Pelaku (Studi Kasus Denny Cagur) - Septian Pratama Putra; Syarif Nurhidayat (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This study analyzes the fulfillment of elements in the alleged criminal act of promoting online gambling in relation to the unawareness claimed by Denny Cagur. This type of research is normative legal research. The approach employed in this study involves statutory and conceptual approaches. The sources of data used in this research are secondary and tertiary data. The findings indicate that Denny Cagur’s claimed unawareness constitutes a right to remain silent (non-self-incrimination). However, it was concluded that Denny Cagur fulfilled all the elements of the criminal offense of promoting online gambling. Furthermore, it was determined that Denny Cagur acted intentionally, as he did not meet the parameters of factual mistake (feitelijke dwaling). Based on the normative concept of guilt (normatief schuldbegrip), public judgment suggests that Denny Cagur deliberately committed the act in question.